2020
DOI: 10.1186/s12966-020-01006-6
|View full text |Cite
|
Sign up to set email alerts
|

Twelve year trajectories of physical activity and health costs in mid-age Australian women

Abstract: Background: Few studies have examined relationships between physical activity (PA) during mid-age and health costs in women. The aim of this study was to investigate associations between PA levels and trajectories over 12 years with medical and pharmaceutical costs in mid-age Australian women. Methods: Data from 6953 participants in the Australian Longitudinal Study on Women's Health (born in 1946-1951) were analysed in 2019. PA was self-reported in 2001 (50-55y), 2007 (56-61y) and 2013 (62-67y). PA data were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“… 26 The recent 12-year trajectories of physical activity and health costs in mid-age Australian women found that maintaining ‘active’ physical activity status was associated with up to 40% lower health costs over 3 years. 12 This study used a ‘lasange plot’, a method of modelling changes in categorical variables in longitudinal studies, which does not offer the flexible of conducting sensitivity analysis based on the exposure variable. 12 Our longitudinal findings appear to be robust to several potential threats from confounding or bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 The recent 12-year trajectories of physical activity and health costs in mid-age Australian women found that maintaining ‘active’ physical activity status was associated with up to 40% lower health costs over 3 years. 12 This study used a ‘lasange plot’, a method of modelling changes in categorical variables in longitudinal studies, which does not offer the flexible of conducting sensitivity analysis based on the exposure variable. 12 Our longitudinal findings appear to be robust to several potential threats from confounding or bias.…”
Section: Discussionmentioning
confidence: 99%
“… 12 This study used a ‘lasange plot’, a method of modelling changes in categorical variables in longitudinal studies, which does not offer the flexible of conducting sensitivity analysis based on the exposure variable. 12 Our longitudinal findings appear to be robust to several potential threats from confounding or bias. Association with Medicare costs by LTPA trajectory patterns were generally similar when more stringent trajectory membership requirements were applied and when we excluded the last 12 months of claims data from each respondent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach still to be further explored in the field of physical activity is the modeling of physical activity trajectories. Recent studies have modeled trajectories of physical activity using a variety of methods 4,5 and investigated whether the risk/protective effect associated with physical activity is different between those who have always been active and those who were always inactive or became inactive. Overall, the findings from these studies have suggested that individuals who were inactive in a period of life but became physically active during mid-age had better health outcomes than those who were always inactive.…”
Section: Many Life Stories In One Time Pointmentioning
confidence: 99%
“…Overall, the findings from these studies have suggested that individuals who were inactive in a period of life but became physically active during mid-age had better health outcomes than those who were always inactive. 4,5 A life course framework is also a powerful tool for better understanding the determinants and social inequalities in physical activity, hence providing important insights into how social inequalities impact the etiology of chronic disease conditions. This has been demonstrated in previous studies that found childhood socioeconomic position may have a lasting impact on physical activity and sedentary behavior even when the adult socioeconomic position is taken into account.…”
Section: Many Life Stories In One Time Pointmentioning
confidence: 99%